FINANCIAL SECURITY AND FINANCIAL RISKS OF THE ENTERPRISE (American Journal of Business Management, Economics and Banking, 2025)
The article is devoted to the problems and essence of financial security, which is considered as one of the most important conditions for ensuring sustainable growth of an enterprise. The relevance of the issue of ensuring the financial security of an enterprise and identifying financial risks is indicated. It is noted that the most important indicator characterizing the measure of financial risk and financial security of an enterprise is its level.